Lytic bone lesions in a patient diagnosed with breast cancer – Sarcoidosis - Ami Schattner; Ina Dubin; Yair Glick; Vladimir Kravtsov (QJM: An International Journal of Medicine, 2026)
Abstract Sarcoidosis is an inflammatory disease of unknown cause with protean manifestations and presentations which may affect almost any organ. Involvement of intra-thoracic organs (lungs, lymph nodes), reticuloendothelial system, skin, and eyes is predominant. The histological hallmark is non-necrotizing (noncaseating) granulomas. Bone involvement in sarcoidosis is noteworthy. We report a woman who developed crescendo back pain, with multiple lytic bone lesions. Since she had been recently diagnosed with locally-invasive breast cancer, metastatic spread was strongly suspected, but prudently, bone biopsy was considered essential. The biopsy was typical of sarcoidosis, later also identified in the lungs/lymph nodes, and successfully treated. Sarcoidosis is a notorious imitator which may pose a substantial diagnostic challenge, especially when presenting as seemingly isolated destructive bone lesions. Its development shortly after breast cancer may be coincidental, but anecdotal data and an observational study suggest that stressful life events affecting the immune system may precede its appearance in some cases.